2014
DOI: 10.7150/ijbs.8737
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Elastase-Pulmonary Emphysema in Dominant-Negative MafB Transgenic Mice

Abstract: Alveolar macrophages (AMs) play important roles in the pathogenesis of chronic obstructive pulmonary disease (COPD). We previously demonstrated upregulation of the transcription factor MafB in AMs of mice exposed to cigarette smoke. The aim of this study was to elucidate the roles of MafB in the development of pulmonary emphysema. Porcine pancreatic elastase was administered to wild-type (WT) and dominant-negative (DN)-MafB transgenic (Tg) mice in which MafB activity was suppressed only in macrophages. We meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…However, we have observed that MCTO mutations limit the acquisition of GM-CSF-inducible genes in GM-MØ, a finding that might be relevant in the case of macrophages whose development is critically dependent on GM-CSF (lung alveolar macrophages) (69). Although no lung-associated pathology has been to date reported in MCTO patients, it is worth noting that a significant number of genes aberrantly expressed in pulmonary diseases (pulmonary sarcoidosis, asthma, and tuberculosis) exhibit an altered expression in MCTO M-MØ, a finding that might be related to the fact that mature alveolar macrophages, identified as intermediate positive for the Emr1-encoded F4/80, are reduced in the bronchoalveolar lavage of mice expressing a dominant-negative MafB in macrophages (70). Given these antecedents, the analysis of further MCTO patients, it is certainly worthy as a means to get a deeper knowledge of the molecular mechanisms operating in this and other related osteolytic syndromes as well as to more clearly delineate the role of MAFB in the acquisition of the human macrophage anti-inflammatory profile.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have observed that MCTO mutations limit the acquisition of GM-CSF-inducible genes in GM-MØ, a finding that might be relevant in the case of macrophages whose development is critically dependent on GM-CSF (lung alveolar macrophages) (69). Although no lung-associated pathology has been to date reported in MCTO patients, it is worth noting that a significant number of genes aberrantly expressed in pulmonary diseases (pulmonary sarcoidosis, asthma, and tuberculosis) exhibit an altered expression in MCTO M-MØ, a finding that might be related to the fact that mature alveolar macrophages, identified as intermediate positive for the Emr1-encoded F4/80, are reduced in the bronchoalveolar lavage of mice expressing a dominant-negative MafB in macrophages (70). Given these antecedents, the analysis of further MCTO patients, it is certainly worthy as a means to get a deeper knowledge of the molecular mechanisms operating in this and other related osteolytic syndromes as well as to more clearly delineate the role of MAFB in the acquisition of the human macrophage anti-inflammatory profile.…”
Section: Discussionmentioning
confidence: 99%
“… 18 In animal models of COPD, it demonstrated that dominant-negative MafB suppressed porcine pancreatic elastase-induced emphysema by downregulating MMPs. 19 Considering the significant role of MMP-9 in the above studies, it may be worthwhile exploring its role in the function of different primary cells from patients with disease.…”
Section: Introductionmentioning
confidence: 99%
“…Since MafB knockout mice die after birth due to developmental anomalies of neurons in the respiratory center [9], we generated transgenic mice with macrophage-specific dominant negative (DN)-MafB by using the macrophage scavenger receptor (MSR) enhancerpromoter [10,11]. A truncated form of MafB lacking an N-terminal acidic domain reportedly acts in a dominant negative manner [4].…”
Section: Introductionmentioning
confidence: 99%